Improving perfomance of Cu2(Zn,Mn)SnS4 thin film solar cell - Sandi, Mario Indra (2017)
Solution processed Cu2ZnSnS4 (CZTS) kesterite thin film serves as an alternative earth abundant, non-toxic and low cost absorber layer for thin film solar cell. However, existence of secondary phases limits the performance of current CZTS below its theoretical Shockley Quiesser power conversion efficiency limit of more than 30%. Existence of low formation energy secondary phase, such as ZnS, restricts optimum light absorption by CZTS which confines the current generated in the device. Introduction of Mn to partially replace Zn is hypothesized to reduce the formation of ZnS secondary phases and improves the power conversion efficiency of CZTS. In this study, solution based Cu2MnxZn1-xSnS has been fabricated with different Mn/Zn ratios to understand the effect of Mn substitution on the device performance and intrinsic properties of the thin film. The study shows enhancement of short circuit current (Jsc) from 14.76 mA/cm2 to 16.63 mA/cm2 which leads to improved efficiency of 5.43% (active area efficiency of 5.88%). X-ray diffraction (XRD) pattern confirms that Mn has substituted for Zn in the crystal lattice of CZTS. Insignificant change in band gap at optimum Mn content is recorded by IPCE measurement while SEM-Energy-dispesive X-ray (EDX) validates the purity and elemental composition of the device. Influence of Mn doping in carrier transport properties is analysed via AC Hall Measurement. Raman spectroscopy is utilized to evaluate existence of secondary phases in different Mn content.